2013
DOI: 10.1158/1078-0432.ccr-12-1515
|View full text |Cite
|
Sign up to set email alerts
|

Progression-Free Survival as a Surrogate Endpoint for Median Overall Survival in Metastatic Colorectal Cancer: Literature-Based Analysis from 50 Randomized First-Line Trials

Abstract: Purpose: To evaluate progression-free survival (PFS) as a potential surrogate endpoint (SEP) for overall survival (OS) in metastatic colorectal cancer (mCRC) with a focus on applicability to trials containing targeted therapy with anti-VEGF-or anti-EGF receptor (EGFR)-directed monoclonal antibodies.Experimental Design: A systematic literature search of randomized trials of first-line chemotherapy for mCRC reported from January 2000 to January 2012 was conducted. Adjusted weighted linear regression was used to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 91 publications
5
32
0
Order By: Relevance
“…Consistent with recent findings (29), our data suggest that in current mCRC treatment regimens, PFS remains strongly correlated with OS. Regardless of this, PFS may reflect clinical benefit on its own, has many intrinsic advantages, and, therefore, should be considered a true primary endpoint in mCRC (30)(31)(32).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with recent findings (29), our data suggest that in current mCRC treatment regimens, PFS remains strongly correlated with OS. Regardless of this, PFS may reflect clinical benefit on its own, has many intrinsic advantages, and, therefore, should be considered a true primary endpoint in mCRC (30)(31)(32).…”
Section: Discussionsupporting
confidence: 93%
“…Using PFS instead of OS as a primary endpoint has accelerated the reporting of results, thus accelerating the introduction of new drugs. Researchers have investigated PFS as a surrogate endpoint for OS with other cancers, validating its use with metastatic colorectal cancer [43,44,45] and breast cancer [44], while questioning its role in trials of molecular targeted agents (e.g., tyrosine kinase inhibitors (TKIs)) [46,47]. PFS has not been fully validated as a surrogate endpoint for OS in MM, and due to the ongoing debate about surrogate endpoints, establishing the usefulness of PFS in predicting OS aids in the rationale for its use as a primary endpoint in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The objective response rate was previously shown to represent a surrogate end point for OS in mCRC [11]; PFS has therefore been widely employed as a primary end point in clinical trials, especially those involving first-line treatments [12,13]. However, a recent comprehensive review demonstrated a weaker correlation between PFS and OS in first-line chemotherapies that involved cetuximab or panutumumab rather than bevacizumab-based or biologic-free regimens [14]. Therefore, novel biomarkers associated with OS are still awaited in the era of molecular targeting therapy for mCRC.…”
Section: Discussionmentioning
confidence: 99%